A cluster-randomised controlled trial of a physical activity and nutrition programme in retirement villages: a study protocol. Issue 9 (25th September 2014) - Holt, Anne-Marie; Jancey, Jonine; Lee, Andy H; Kerr, Deborah A; Hills, Andrew P; Anderson, Annie S; Howat, Peter A
Abstract : Introduction: Physical activity levels of Australia's ageing population are declining and coincidentally rates of overweight and obesity are increasing. Adequate levels of physical activity and a healthy diet are recognised as important lifestyle factors for the maintenance of a healthy weight and prevention of chronic diseases. Retirement village (RV) residents rarely engage in physical activity and nutrition programmes offered, with poor attendance and low use of existing facilities such as on-site fitness centres and classes and nutrition seminars. The RV provides a unique setting to access and engage with this older target group, to test the effectiveness of strategies to increase levels of physical activity, improve nutrition and maintain a healthy weight. Method and analysis: This cluster-randomised controlled trial will evaluate a physical activity, nutrition and healthy weight management intervention for insufficiently active ('not achieving 150 min of moderate-intensity physical activity per week') adults aged 60–75 residing in RV's. A total of 400 participants will be recruited from 20 randomly selected RV's in Perth, Western Australia. Villages will be assigned to either the intervention group (n=10) or the control group (n=10) each containing 200 participants. The Retirement Village Physical Activity and Nutrition for Seniors (RVPANS) programme is a home-based physical activity and nutrition programme that includes educational resources, along with facilitators who will motivate and guide the participants during the 6-month intervention. Descriptive statistics and mixed regression models will be performed to assess the intervention effects. This trial will evaluate an intervention for the modification of health risk factors in the RV setting. Such research conducted in RV's has been limited. Ethics and dissemination: Curtin University Human Research Ethics Committee (approval number: HR128/2012). Dissemination of the study results will occur through publications, reports, conference presentations and community seminars. Trial registration number: Australia and New Zealand Clinical Trial Registry (ACTRN12612001168842)